2018
DOI: 10.1186/s40661-018-0060-6
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic characteristics influencing cervical cancer screening intention of HIV-positive women in the central region of Ghana

Abstract: BackgroundThe burden of HIV and cervical cancer is concentrated in sub-Saharan Africa. Women with HIV are more likely to have persistent HPV infection leading to cervical abnormalities and cancer. Cervical cancer screening seems to be the single most critical intervention in any efforts to prevent cervical cancer. The purpose of this study was to determine the socio-demographic factors influencing intention to seek cervical cancer screening by HIV-positive women in the Central Region of Ghana.MethodsA descript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 38 publications
(42 reference statements)
5
17
1
Order By: Relevance
“…This systematic review and meta-analysis revealed that HIV-positive women having formal education were 3.50 times more likely to be screened for cervical cancer as compared with HIV-positive women who have no formal education. This finding was supported by previous studies [ 44 , 53 , 54 ]. The reason could be the fact that women who are educated have better understanding of the cause, risk factors, prevention mechanism, and treatment of the disease given from healthcare workers, mass media, and different stakeholder.…”
Section: Discussionsupporting
confidence: 92%
“…This systematic review and meta-analysis revealed that HIV-positive women having formal education were 3.50 times more likely to be screened for cervical cancer as compared with HIV-positive women who have no formal education. This finding was supported by previous studies [ 44 , 53 , 54 ]. The reason could be the fact that women who are educated have better understanding of the cause, risk factors, prevention mechanism, and treatment of the disease given from healthcare workers, mass media, and different stakeholder.…”
Section: Discussionsupporting
confidence: 92%
“…That is, women who had post-primary level of education are more likely to use CCS services than those with no formal education levels. The same finding was observed in studies done in, India [29], Nigeria [30], Ghana [31], Gondar [18] and Addis Ababa [19], in which level of education can predict CCS. Similarly, a study conducted in Italy [32] reported lack of Pap-smear in the last year was significantly associated with lower educational level.…”
Section: Discussionsupporting
confidence: 85%
“…An outcome which was not consistent with the current study. However, a study conducted in Ghana showed that marital status is not a statistically significant determinant of women' intention to have CC screening [48]. Thus the influence of marital status on CC screening appears to be inconsistent across studies.…”
Section: Plos Onementioning
confidence: 98%
“…Similarly, a study in Ethiopia said that women who were employed were four times more likely to utilize CC screening services [47]. However, amongst HIV patients, a study conducted in Ghana indicated that employment was not expected to affect the intention to have CC screening [48]. A possible explanation to this finding could be attributed to the fact that women who are employed have the financial ability to afford the cost of screening or perhaps they are keen on their health to be able to continue their work.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation